Constraining the Oceanic Uptake and Fluxes of Greenhouse Gases by Building an Ocean Network of Certified Stations: The Ocean Component of the Integrated Carbon Observation System, ICOS-Oceans - Steinhoff, Tobias; Gkritzalis, Thanos; Lauvset, Siv K.; Jones, Steve; Schuster, Ute; Olsen, Are; Becker, Meike; Bozzano, Roberto; Brunetti, Fabio; Cantoni, Carolina; Cardin, Vanessa; Diverrès, Denis; et al. (Frontiers in Marine Science, 2019)
ICOS-Oceans is the marine domain of the European Research Infrastructure Consortium “Integrated Carbon Observation System” (ICOS). It aims at delivering high quality greenhouse gas (GHG) observations and derived data products (e.g. regional GHG-flux maps) for constraining the GHG balance on a European level, on a sustained long-term basis. ICOS-Oceans currently consists of 11 Ship of Opportunity lines (SOOP – Ship of Opportunity Program) and 10 Fixed Observation Stations (FOS) spread across European waters, including the North Atlantic Ocean and the Barents, North, Baltic and Mediterranean Seas. The stations operate in a harmonised and standardised way based on community-proven protocols and methods for ocean GHG observations improving operational conformity as well as quality control and assurance of the data. This enables the network to focus on long term research into the marine carbon cycle and the anthropogenic carbon sink, while preparing the network to include other GHG fluxes. ICOS data are processed on a near real-time basis and will be published on the ICOS Carbon Portal, allowing monthly estimates of CO2 air-sea exchange to be quantified for European waters. ICOS establishes transparent operational data management routines following the FAIR (Findable, Accessible, Interoperable and Reusable) guiding principles allowing amongst others reproducibility, interoperability and traceability. The ICOS-Oceans network is actively integrating with the atmospheric (e.g. improved atmospheric measurements onboard SOOP lines) and ecosystem (e.g. oceanic direct gas flux measurements) domains of ICOS, and utilises techniques developed by the ICOS Central Facilities and the Carbon Portal. There is a strong interaction with the international ocean carbon cycle community to enhance interoperability and harmonise data flow. The future vision of ICOS-Oceans includes ship-based ocean survey sections to obtain a 3-dimensional understanding of marine carbon cycle processes and optimise the existing network design.